Calendar effects in daily aggregate employment creation and destruction in Spain - J. Ignacio Conde-Ruiz; Manu García; Luis Puch; Jesús Ruiz (SERIEs - Journal of the Spanish Economic Association, 2019)
In this paper, we discuss the time series properties of a novel daily series of aggregate employment creation and destruction as registered by the Social Security in Spain. We focus on the period of economic recovery after the 2012 Labour Market Reform. Our concern for high-frequency data is motivated by the recent upsurge of labour contracts of a very short duration, which seems to have exacerbated the spikes in employment flows over the calendar year. First, we identify calendar effects in job flows and single out the Monday effect: an overreaction in job creation at the beginning of the workweek. Then, we investigate the importance of calendar effects for aggregate employment dynamics. We find that the employment growth rate shows a systematic decrease by the end of each month, which is more pronounced during the second half of the year, and it intensifies as the economy moves further along the expansion period. Finally, we use the flow of contract records at the micro-level (several millions) to evaluate how the occupational structure determines employment spikes. Our findings indicate that short-term contracts are highly prevalent in occupations under stronger calendar effects. In particular, we show that temporary workers' contracts are the most important source of the Monday effect.
Keywords: J23; E24; C22; 330; Employment flows; Fixed-term contracts; Calendar effects; Business cycle fluctuations; Sectoral composition; Regime shifts